Risk-factor differences for nonsuicidal self-injury and suicide attempts in Mexican psychiatric patients - Fresán A; Camarena B; González-Castro TB; Tovilla-Zarate CA; Juárez-Rojop IE; López-Narvaez ML; González-Ramón AE; Hernandez-Díaz Y (Neuropsychiatric Disease and Treatment, 2016)
Ana Fresán,1 Beatriz Camarena,2 Thelma Beatriz González-Castro,3 Carlos Alfonso Tovilla-Zárate,4 Isela E Juárez-Rojop,5 Lilia López-Narváez,5 Alicia E González-Ramón,4 Yazmín Hernández-Díaz3 1Subdirección de Investigaciones Clínicas, Instituto Nacional de Psiquiatría Ramón de la Fuente Muñiz, México City, 2Departamento de Genética Psiquiátrica, Instituto Nacional de Psiquiatría Ramón de la Fuente Muñiz, México City, 3División Académica Multidisciplinaria de Jalpa de Méndez, Universidad Juárez Autónoma de Tabasco, Jalpa de Méndez, 4División Académica Multidisciplinaria de Comalcalco, Universidad Juárez Autónoma de Tabasco, Comalcalco, 5Hospital General de Yajalón, Secretaría de Salud, Yajalón, Chiapas, México Background: The present study compared sociodemographic characteristics, comorbidities with substance use, and impulsivity features in three groups of psychiatric patients – suicide attempters, nonsuicidal self-injury, and nonsuicidal without self-injury – to determine the predictive factors for nonsuicidal self-injury or suicide behavior.Patients and methods: Demographic features and self-reported substance use were assessed in 384 Mexican psychiatric patients. Impulsivity features were evaluated using the Plutchik Impulsivity Scale. Comparison analyses between groups were performed and a logistic regression model used to determine the factors associated with nonsuicidal with self-injury behavior and suicidal behavior.Results: Different predictive factors were observed for nonsuicidal self-injury and suicidal behavior. Females were more likely to present nonsuicidal self-injury behaviors (odds ratio [OR] 0.42, 95% confidence interval [CI] 0.18–0.93; P=0.03). For suicide attempters, the factors associated were younger age (OR 0.89, 95% CI 0.85–0.93; P<0.001), less than 6 years of schooling (OR 0.2, 95% CI 0.06–0.6; P=0.004), and higher impulsivity traits, such as self-control (OR 1.19, 95% CI 1.03–1.36; P=0.01), planning of future actions (OR 0.79, 95% CI 0.66–0.95; P=0.01), and physiological behavior (OR 1.34, 95% CI 1.01–1.78; P=0.03).Conclusion: Our results show that in a Mexican population, impulsivity features are predictors for suicide attempts, but not for self-injury. Other factors related to sociocultural background and individual features (such as personality) may be involved in this behavioral distinction, and should be studied in future research aimed at better understanding of both self-harmful behaviors. Keywords: suicide, impulsivity, Mexican population, self-injury